Temporal dynamics of gene expression and histone marks at the Arabidopsis shoot meristem during flowering - Yuan You (Nature Portfolio, 2017)
When plants flower, the shoot apical meristem switches fate to produce floral organs instead of leaves. Here Youet al. perform tissue-specific epigenome profiling and show that during this transition changes in histone methylation are correlated with transcriptional responses in the meristem.